2020
DOI: 10.1111/1440-1703.12165
|View full text |Cite
|
Sign up to set email alerts
|

How plant–soil feedbacks influence the next generation of plants

Abstract: In response to environmental conditions, plants can alter the performance of the next generation through maternal effects. Since plant-soil feedbacks (PSFs) influence soil conditions, PSFs likely create such intergenerational effects. We grew monocultures of three grass and three forb species in outdoor mesocosms. We then grew one of the six species, Hypochaeris radicata, in the conditioned soils and collected their seeds. We measured seed weight, carbon and nitrogen concentration, germination and seedling per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…5 and 6 ). Several recent studies indicated that soil legacy, including the microorganisms originating from past vegetation, influences the succession of the next generations of plants by altering the germination rate and plant growth ( 51 53 ). We thus hypothesize that the transfer of potentially beneficial microorganisms among different generations of plants could be important in contaminated soils, including those in extreme environments.…”
Section: Discussionmentioning
confidence: 99%
“…5 and 6 ). Several recent studies indicated that soil legacy, including the microorganisms originating from past vegetation, influences the succession of the next generations of plants by altering the germination rate and plant growth ( 51 53 ). We thus hypothesize that the transfer of potentially beneficial microorganisms among different generations of plants could be important in contaminated soils, including those in extreme environments.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor can be maternal effects: The phenotype of plants is dependent on the conditions which the mother has experienced (Herman & Sultan, 2011;De Long et al, 2019;De Long et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…(2019). In addition to this, the lower performance of plants in away‐same than in home soil highlights that both plant species diversity and plant species composition determine plant–soil feedback effects and thus the selection environment (De Long et al., 2020; He & Lamont, 2010). Nevertheless, we can only speculate about the exact reasons for the home advantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental effects and soil legacy effects resulting from environment changes are most likely to act simultaneously in mediating plant performance and plant community dynamics (De Long et al, 2021). However, parental effects and soil legacy effects are typically tested independently, and we lack the knowledge on how they may interact to influence plant performance (but see De Long et al, 2019, 2021).…”
Section: Introductionmentioning
confidence: 99%